Designing Authentic EFL Listening and Speaking Materials Using CEFR Framework - Ramadhani, Amanda Agni Oktavia; Maisarah, Maisarah; Amalia, Najwa; Widiastuty, Hesty (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This conceptual study addresses the gap by proposing an integrated model that combines receptive and productive skills within a unified CEFR-based instructional sequence. The study outlines structured stages consisting of pre-, while-, and post-listening phases accompanied by communicative speaking tasks such as role plays, collaborative problem-solving, and short oral presentations. The proposed model underscores the pedagogical importance of connecting authentic input with meaningful output while utilizing CEFR descriptors as evaluation benchmarks. Consequently, this study contributes to both pedagogical and policy perspectives by offering a framework that enhances communicative competence and strengthens the international alignment of English language education in Indonesia.